The State Industrial Policy in Modern Conditions: World Experience - Y. V. Mishalchenko; A. V. Toropygin (Евразийская интеграция: экономика, право, политика, 2019)
In article the characteristic is given to the main tendencies and the directions of realization of the state industrial policy in the advanced industrial countries (Great Britain, Germany, Austria, Japan). Strategy of the state industrial policy of the CIS countries in system of the Euroasian integration are formulated. The concept of the state industrial policy of the CIS countries in modern conditions of development of world economy is offered